Pengaruh Financial Literacy Terhadap Bank’s Performance di Indonesia - Fry Melda Saragih; Debi Eka Putri; Yenny Wati; Nelly Ervina (Universitas Negeri Padang, 2023)
This study explores the effect of financial literacy on bank's performance in Indonesia using the measurement dimensions of financial attitude, financial knowledge and financial capability. This quantitative research adopted a cross-sectional research design to collect data from 257 respondents using Google Form. The collected data were analysed using partial least squares structural equation modelling (PLS-SEM). As a result, financial attitude and financial capability showed a significant positive influence on financial literacy and bank's performance. In addition, financial literacy also shows a significant positive influence on bank's performance. Meanwhile, financial knowledge has no significant influence on financial literacy and bank's performance. This study proved the mediating effect of financial literacy on the correlation between financial attitude and financial capability. However, financial literacy has no mediating effect on financial knowledge. The results of this study serve to inform customers, managers and policy makers in Indonesian banks to design effective strategies on how important financial literacy is in today's volatile market. Ultimately, providing financial literacy knowledge to customers can have a good impact on bank performance, in addition to making customers more financially literate and able to make good financial decisions.